Bread : A Memoir of Hunger - Knopp, Lisa, 1956- (Book collections on Project MUSE., 2016)
"When she was 54, Lisa Knopp's weight dropped to a number on the scale that she hadn't seen since seventh grade. The severe food restricting that left her thin and sick when she was 15 and 25 had returned. But this time she was determined to understand the causes of her "malady" and how she could heal from a condition that is caused by a tangle of genetic, biological, familial, psychological, cultural, and spiritual factors. This compelling memoir, at once a food and illness narrative, explores the various forces that cause eating disorders and disordered eating, including the link between those conditions in women, middle-aged and older, and the fear of aging and ageism"--Publisher's description